Fracture Characteristics and its Role in Bedrock Reservoirs in the Kunbei Fault Terrace Belt of Qaidam Basin, China - Wang, Zhaosheng; Xiang, Hui; Wang, Libin; Xie, Lin; Zhang, Zhenguo; Gao, Lianfeng; Yan, Zhifeng; Li, Fuling (Frontiers in Earth Science, 2022)
Fracture characteristics at bedrock reservoirs in the Kunbei fault terrace belt in the southwest of Qaidam Basin, China, are investigated based on cores, thin sections, formation microscanner imaging, and production data. Results show that the weathered unit at the top of bedrocks is not an effective reservoir because of extremely low porosity. A semi-weathered unit is a potential reservoir, where formation water migrating along early effective fractures could form dissolution fractures and pores as primary storage space, and fractures can also act as seepage channels. Four fracture types can be identified from bedrock reservoirs, e.g., structural ones, diagenetic ones, weathering ones, and dissolution ones, while shear fractures related to faults are the most important ones. Fracture types and characteristics are different in granite and slate, e.g., high fracture density results in intensive dissolution in granite. Fracture density is closely related to tectonic stress. The bedrock reservoirs near fault zones and semi-weathered units are potential oil and gas exploration targets in the Kunbei fault terrace belt. Effective fractures govern dissolution behaviors as well as dominant seepage directions, which play a significant role in the development of bedrock reservoirs.